Experimental Study on Mechanical Properties and Energy Evolution Law of Coal-Rock Composite Structure under Different Interface Connection Modes - Chenglin Tian; Haitao Sun; Linchao Dai; Rifu Li; Bo Wang; Jie Cao; Jun Wang; Qianting Hu (Geofluids)
The stability of the coal-rock composite structure is of great significance to the safety production of deep mines, and the different interface connection modes of coal and rock have an important influence on its stability. Therefore, the following work was done in this article: Firstly, the mechanical structure model of coal-rock was established, and the influence of different interface connection modes on coal rock was analyzed. Secondly, the mechanical characteristics (plastic zone, stress, and displacement) of coal-rock composite structure under different interface connection modes were studied by numerical simulation, and the energy was quantitatively analyzed by FISH language in FLAC3D. The results were as follows: (1) The interface reduces the strength of rock and increases the strength of coal in the coal-rock composite structure. (2) In the loading process, the coal body is destroyed first and the destruction range increases gradually with the increase of stress. The failure mode is mainly a plastic shear failure, and the deformation of coal is much larger than that of rock in the composite structure. (3) The interface contact mode affects the mechanical behavior of coal and rock structure. The strong contact interface influences the strength, displacement, and energy accumulation of coal and rock structure, among which the influence on energy and displacement is greater, which is helpful to the improvement of strength. Therefore, it is suggested to adopt the strong contact interface in the study of coal and rock structure.